Arterial Blood Pressure and Heart Rate Response to Exercise - A. Subradeepan2, W. Vinu2; Y. Wise Blessed Singh2, K. Jothi1, (Recent Research in Science and Technology, 2011)
The current investigation is likely to illuminate the variableness on arterial blood pressure and heart rate in response to exercise. For this purpose, fifteen male kabaddi players in the age group of 20 to 25 years were selected as subjects from Annamalai University, during their competitive season. The selected dependent variables such as (systolic blood pressure, diastolic blood pressure, mean arterial pressure and heart rate) were appraised using Oscillometric method and instruments of scientific standards at resting conditions and after exercise. To statistically analyse and compare the changes on arterial blood pressure and heart rate response to exercise, ‘t’ test was used. The analysis of data revealed that there is a significant magnification on systolic, diastolic, mean arterial pressure and heart rate in response to exercise. These findings suggest that exercise induces significant transformation in cardiovascular variables.